A quantum modal realist solution to the Grandfather Paradox - Santos, Gabriel Lee Mac Fadden (2023)
The Grandfather Paradox has seen many different solutions, but none that is fully satisfactory. This work is a new attempt to show how backward time travel is possible but with recourse to non-traditional metaphysical tools. My main thesis is that Quantum Modal Realism (QMR) – a metaphysical theory based on Everettian Quantum Mechanics – both conflicts with most of the previous solutions to the Paradox, but also entails a simple, modal realist final answer to the problem. Briefly put, QMR simplifies the assessment of whether a time traveler has the ability to perform grandpatricide (or any other similar kind of temporal murder). The conclusion is negative, with the caveat that backward time travel is still possible. Once this problem is dealt with, QMR also explains what would happen if someone insisted on trying to commit grandpatricide despite the knowledge that it never works. As a reply, I appeal to one’s intuitions and argue that the act of trying to perform that murder, in fact, would amount to nothing.